2015
DOI: 10.1007/s00198-015-3356-y
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical utility of routine laboratory testing to identify possible secondary causes in older men with osteoporosis: the Osteoporotic Fractures in Men (MrOS) Study

Abstract: Purpose To evaluate the utility of recommended laboratory testing to identify secondary causes in older men with osteoporosis, we examined prevalence of laboratory abnormalities in older men with and without osteoporosis. Methods 1572 men aged ≥65 years in the Osteoporotic Fractures in Men study completed bone mineral density (BMD) testing and a battery of laboratory measures, including serum calcium, phosphorus, alkaline phosphatase, parathyroid hormone (PTH), thyroid-stimulating hormone (TSH), 25-OH vitami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 15 publications
1
29
0
Order By: Relevance
“…Sundh et al emphasized that serum vitamin D is associated with higher cortical porosity in elderly men (30). Other studies also revealed the importance of vitamin D deficiency in male osteoporosis (12,15,19,31). The provinces where our study was performed are disadvantaged areas in terms of climate characteristics and insufficient sun exposure, when evaluated with regard to vitamin D synthesis.…”
Section: Resultsmentioning
confidence: 73%
“…Sundh et al emphasized that serum vitamin D is associated with higher cortical porosity in elderly men (30). Other studies also revealed the importance of vitamin D deficiency in male osteoporosis (12,15,19,31). The provinces where our study was performed are disadvantaged areas in terms of climate characteristics and insufficient sun exposure, when evaluated with regard to vitamin D synthesis.…”
Section: Resultsmentioning
confidence: 73%
“…20 In that cohort men with osteoporosis more often had a history of fractures or kidney stones. However, among more than 300 men with both BMD and 24-hour urine calcium no relationship was found between urinary calcium and osteoporosis.…”
Section: Discussionmentioning
confidence: 94%
“…Usually, serum ALP is used as an indicator of bone formation in mammalian bone research [Halling et al, ; Fink et al, ]. ALP could be produced in liver, bone, intestine, and kidney, and about 50% of total ALP was produced from bone in healthy adults [Kuo and Chen, ].…”
Section: Discussionmentioning
confidence: 99%